Why Grexit cannot save Greece (but staying in the Euro area might) - Chrysafis Iordanoglou; Manos Matsaganis (London School of Economics and Political Science (LSE), European Institute, 2017)
Grexit was narrowly averted in summer 2015. Nevertheless, the view that Greece might be better off outside the Euro area has never really gone away. Moreover, although Marine Le Pen's bid for the French presidency was frustrated in May 2017, in Italy a disparate coalition, encompassing Beppe Grillo's Movimento Cinque Stelle as well as Matteo Salvini's Lega Nord, has called for a referendum on exiting the Euro. In this context, our argument that Grexit cannot save Greece may be of some relevance to national debates elsewhere in Europe. The paper examines the case for Grexit by offering a detailed account of its likely effects. Its structure is as follows. Section 2 analyses the transition, with the two currencies (old and new) coexisting. Section 3 charts the challenges facing the Greek economy in the short term, after the new national currency has become legal tender. Section 4 assesses prospects in the medium term, with Grexit complete and the new currency drastically devalued. Section 5 reviews the underlying weaknesses of Greece's growth regime and explains why these are unrelated to the nominal exchange rate. Section 6 discusses the conditions for an investment-led recovery, and shows why tackling them would be more difficult outside the Euro area. Section 7 sums up and concludes.
Keywords: 330; Greece; Grexit; Eurozone; growth regime